The Relationship between Primary Acquired Nasolacrimal Duct Obstruction and Gastroesophageal Reflux. (3rd October 2018) - Owji, Naser; Radaei, Mohammad; Khademi, Behzad
ABSTRACT: Purpose/Aim of the study : To evaluate if there is any relationship or coincidence between gastroesophageal reflux disease (GERD) and primary acquired nasolacrimal duct obstruction (PANDO). Material and Methods : We enrolled 180 patients with PANDO, confirmed by positive regurgitation on sac squeezing or by irrigation test. In the control group, any patient with lacrimal drainage obstruction was excluded. For diagnosis of gastroesophageal reflux we used a (Gerd Q) questionnaire by R. Jones. Results : According to Gerd Q, prevalence of gastroesophageal reflux in patients with PANDO was 20% (36 out of 180 patients) and in the control group, it was 10.6% (19 out of 180 patients), which was significantly higher in the presence of PANDO ( p valve = 0.013). In women, 28 patients (23.5%) in the case group versus 13 patients (10.9%) in the control group has gastroesophageal reflux ( p value = 0.01), which was not significant among men ( p value = 0.870). When we considered age as an independent variable, results reveled significant value only for patients over 60 years old ( p value = 0.008). Conclusion : The prevalence of gastroesophageal reflux disease was significantly higher in patients with PANDO. This statistical relationship was greater among women and patients over 60 years old. In this study, we found an association between GERD and PANDO.